PENGARUH PUPUK HIJAU Azolla microphylla DAN NPK TERHADAP PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.) FASE MAIN NURSERY - Robby ' Heriyanto; Idwar ' '; Erlida ' Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to determine the effect of the interaction and the single factor green manure, Azolla microphylla and NPK fertilizer on plant oil palm in the main nursery as well as getting the best dose. This research has been conducted in the experimental garden of Faculty of Agriculture, University of Riau in November 2015 to March 2016. The study was conducted experimentally using a completely randomized design (CRD) factorial, consisting of two factors and three replications. The first factor is Green manure Azolla Microphylla with 6 levels (0, 20, 40, 60, 80 and 100 / polybag) and the second factor is NPK fertilizer with 4 levels (0, 10, 20 and 30 g / polybag). The parameters measured were the increase of plant height, , in the number of leaves, stem diameter increase, root volume, dry weight, the uptake of N in the leaves and the leaves outbreak. The results were analyzed statistically using Analysis Of Variance (ANOVA). The results of the analysis of the test manifold followed by Duncan's New Multiple Range Test (DNMRT) level of 5%. The results showed that administration of green manure, Azolla microphylla and NPK on oil palm seedlings no real effect on the increase of plant height, stem diameter increase, in the number of leaves root volume and dry wight . In morphology, palm trees aged 7 months treated green manure Azolla microphylla and NPK grow well, but development in general leaves only reached the stage of development bifurcate. Oil palm seedlings were given the green manure Azolla microphylla with a dose of 40 g / polybag and NPK at a dose of 10 g / polybag provide good seedling growth and nutrient uptake of N highest. Keywords: Azolla microphylla, NPK fertilizer and oil palm seedlings